Analysis of factors related to self-care in chronic heart failure patients in Indonesian - Tobi Pitora; Tuti Pahria; Eka Afrima Sari (Universitas Muhammadiyah Semarang, 2022)
Chronic Heart Failure (CHF) has impacted changes in physiological and psychological status and has a high risk of death and recurrence. Self-care is one of the efforts that get resolved to prevent recurrence in CHF patients. This study aims to determine factors related to self-care in CHF patients. This study used a descriptive correlational method with a cross-sectional approach. The sample in this study was 74 respondents who were diagnosed with CHF. Collected data in this study using a questionnaire. Data collected were analyzed using univariate, bivariate, and multivariate make use of Pearson's product-moment correlation test and multiple linear regression with the SPSS version 25 application. The study showed that most respondents who experienced CHF were male (70.3%), with the average respondent being 52 years old. The majority of respondents' education is in high school (63.5%) with an average knowledge of 10.76, self-efficacy of 35.00, social support of 77.05, and self-care of 69.66. The results of the bivariate test showed that there was a significant relationship between age (r = 0.281, p < 0.05), education (r = 0.312, p < 0.05), knowledge (r = 0.238, p < 0.05), self-efficacy (r = 0.321, p <0.05) and social support (r=0,239,p<0,05) for self-care in CHF patients. Multivariate analysis showed that self-efficacy was the most dominant factor (β=0.339) related to self-care in CHF patients. Self-efficacy has an important role in CHF patients in carrying out self-care, improve self-efficacy could be done by providing education and motivation, and support to patients in carrying out the treatment process.